Measuring Nutrition and Food Literacy in Adults: A Systematic Review and Appraisal of Existing Measurement Tools - Eva Y. N. Yuen; Maria Thomson; Heather Gardiner (SLACK Incorporated, 2018)
Background: Nutrition literacy (NL) and food literacy (FL) have emerged as key components in the promotion and maintenance of healthy dietary practices. However, a critical appraisal of existing tools is required to advance the operationalization and measurement of these constructs using instruments that demonstrate sound validity and reliability. Methods: Electronic databases were searched in January and July 2016, January 2017, and March 2018 for publications detailing the development and/or testing of NL or FL instruments. Instruments' psychometric properties were assessed using a structured methodological framework. We identified 2,563 new titles and abstracts, and short-listed 524 for full review. The extent to which key domains of NL were included in each measure was examined. Key Results: Thirteen instruments assessing NL underwent full evaluation; seven from the United States, and one each from Australia, Norway, Switzerland, Italy, Hong Kong, and Japan. Measures targeted general Spanish-, Italian-, or Cantonese-speaking adults; primary care patients, parent, and populations with breast cancer. Instruments ranged from 6 to 64 items, and they predominantly assessed functional NL rather than broader domains of NL. Substantial variation in methodological rigor was observed across measures. Discussion: Multidimensional and psychometrically sound measures that capture broader domains of NL and assess FL are needed.